2010
DOI: 10.1163/187502310791305864
|View full text |Cite
|
Sign up to set email alerts
|

From nation-building to desecuritization in Bosnia and Herzegovina

Abstract: This article analyzes the value and impact of the nation building policy of the international community in Bosnia and Herzegovina (Bosnia). The analysis shows that the nation building effort has failed in the sense that the ethnic nationalist political culture persisted and that a collective Bosnian identity is absent. Bosnian politics continued to be dominated by ethnic nationalist political parties and ethnic group interests. The author argues that this can be explained by the continued securitization of eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Beyond the dominant International Relations (IR) approach developed by the 'Copenhagen School', this article understands securitisation as a multifaceted process involving more than a speech act, and it is thus more closely aligned with the practice-oriented securitisation scholarship mostly associated with the sociological approach of the 'Paris School' (Balzacq, 2005;Bigo 2002;Huysmans, 2011). Furthermore, in relation to the specific application of securitisation to minority issues, scholars have tended to focus on how minorities have been securitised and on the role of securitising agents in ethnic conflict (Carlà, 2021;Olesker, 2014;van Willigen, 2010). Accordingly, this article reflects primarily on the role of legislation (Basaran, 2010), key instruments, and political practices that have affected Kosovo minorities in securitising processes, as well as their impact on the feasibility of desecuritisation.…”
Section: Securitisation Of Minorities In Plural Societiesmentioning
confidence: 97%
“…Beyond the dominant International Relations (IR) approach developed by the 'Copenhagen School', this article understands securitisation as a multifaceted process involving more than a speech act, and it is thus more closely aligned with the practice-oriented securitisation scholarship mostly associated with the sociological approach of the 'Paris School' (Balzacq, 2005;Bigo 2002;Huysmans, 2011). Furthermore, in relation to the specific application of securitisation to minority issues, scholars have tended to focus on how minorities have been securitised and on the role of securitising agents in ethnic conflict (Carlà, 2021;Olesker, 2014;van Willigen, 2010). Accordingly, this article reflects primarily on the role of legislation (Basaran, 2010), key instruments, and political practices that have affected Kosovo minorities in securitising processes, as well as their impact on the feasibility of desecuritisation.…”
Section: Securitisation Of Minorities In Plural Societiesmentioning
confidence: 97%
“…Securitisation has become a recurrent theme in regard to both 'old' (national, ethnic, linguistic, and religious) minorities as well as research on 'new' minority communities stemming from recent migratory flows. 1 The securitisation concept has been applied to studies on ethnic conflict and politics of ethno-nationalism, showing how specific national minorities, like Palestinian citizens of Israel, have been securitized; or how all parties involved in tensions/conflicts, as in the case of Northern Ireland, address these tensions in terms of security and act as securitising actors (Fabricius, 2013;Olesker, 2014;Van Willigen, 2010). Within migration studies, scholars have shown how various segments of the migrant population (from undocumented migrants to asylum seekers and second/third generations) have been framed in political discourses, media, or government practices as a threat to states' cultural identity and/or their political, economic, and welfare systems (e.g., Huysmans, 1995).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Second, a growing number of studies have applied securitization to minority issues. However, such work tends to focus on how minorities and specific communities are perceived as a threat, become target of illiberal policies, and/or cause ethnic tensions (Olesker 2014;van Willigen 2010). By focusing on borders, I highlight the boundary-making dynamic that is inherent in securitization processes and its effect on majority-minority relations.…”
Section: Introductionmentioning
confidence: 99%